THE EFFECT OF PROBLEM BASED LEARNING APPROACH AND PLAYING METHOD AND NUTRITIONAL STATUS ON MOTOR ABILITY OF STATE ELEMENTARY SCHOOL - Visano, Diski; Gusril, Gusril; Syahara, Sayuti; Putra, Aldo Naza; Ockta, Yovhandra (STKIP Singkawang, 2024)
The problem in this study is the lack of motor skills. This study aims to determine the effect of problem based learning and playing methods and nutritional status on motor skills of Elementary School 12 Mandau, Bengkalis RegencyThis study uses an experimental method that uses a treatment design with a level of two x two, namely a factory experiment involving two factors. The sample in this study were 20 students of Elementary School 2 Mandau. Nutritional status data were taken by means of tests and measurements using the Body Mass Index (BMI) instrument and to measure motor ability tests using the